PROBLEMS AND NECESSITY OF «GREEN FINANCING» IN THE POST-WAR REBUILDING PERIOD THE ECONOMY OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2022)
In the conditions of war, environmental and security risks increase, hazardous military waste are generated, as a result, pollution occurs due to the destruction of transport and industrial infrastructure. Therefore, the study of the problems of "green" financing and the expediency restoring, first of all, those large budget-generating enterprises is important and relevant.The purpose of the article. The purpose of the article is to reveal the features of "green" financing for the reconstruction of Ukraine's economy after the war with Russia and directions for compliance with the European Union's normative documents.It has been studied that the new form of «green» financing in Ukraine after the war should be the joint allocation by the state, territorial communities and business of funds for the creation of eco-industrial parks in the regions, especially in those affected by Russian aggression. In the structure of «green» finances in Ukraine, the finances of foreign investors should occupy an important place. For the latter should be provided significant financial benefits, primarily tax benefits. At the same time, in order to eliminate corruption, it is important to strengthen public and state financial control over the implementation of «green» projects with foreign investments. In general, when rebuilding the Ukrainian economy, it is important to adhere to European environmental standards to the maximum extent possible.It is proposed to improve the mechanism of "green" financing for the reconstruction of Ukraine's economy and to ensure the active attraction of foreign investments from democratic countries of the world and international financial organizations.
Keywords: «green financing», reconstruction of the economy of Ukraine, climate investments, «green» tariff, European Union, Ukraine